2020
DOI: 10.3390/s20051291
|View full text |Cite
|
Sign up to set email alerts
|

Study of Postural Stability Features by Using Kinect Depth Sensors to Assess Body Joint Coordination Patterns

Abstract: A stable posture requires the coordination of multiple joints of the body. This coordination of the multiple joints of the human body to maintain a stable posture is a subject of research. The number of degrees of freedom (DOFs) of the human motor system is considerably larger than the DOFs required for posture balance. The manner of managing this redundancy by the central nervous system remains unclear. To understand this phenomenon, in this study, three local inter-joint coordination pattern (IJCP) features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…A total number of 13 articles were included for the assessment of posture abnormality or disorder. Some of the reviewed articles [42,46,50,51] did not state the participants in the studies. In Table 4, Kinect v2 was mostly used for skeletal data capturing, except in a few studies that used Kinect v1.…”
Section: Resultsmentioning
confidence: 99%
“…A total number of 13 articles were included for the assessment of posture abnormality or disorder. Some of the reviewed articles [42,46,50,51] did not state the participants in the studies. In Table 4, Kinect v2 was mostly used for skeletal data capturing, except in a few studies that used Kinect v1.…”
Section: Resultsmentioning
confidence: 99%
“…Using joint motion trajectories instead of COP or COM displacement for analysis enables the evaluation of posture control ability as well as the posture control strategies used to achieve balance [ 45 , 46 ]. In the current study, the JNPs of the elderly group indicated that they tended to use an extreme joint coordination mode, an inter-joint coordination strategy characterized by total joint dependence, to maintain balance when standing still [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kinect’s kinematic information is generally accurate enough for ergonomic assessments [ 18 ]. Postural control is the coordination of multiple joints to maintain postural stability, and the device can be used to collect large amounts of joints data to explore the coordinated relationships among the joints of the whole body during the maintenance of postural control [ 19 ]. Kinect’s kinematic parameters follow joint trajectories and, thus, can be used as a tool for measuring spatiotemporal aspects of postural control.…”
Section: Introductionmentioning
confidence: 99%
“…It is responsible for the control of reflex reactions of the body [ 6 ] and the return of the body’s center of gravity to its balance [ 7 , 8 ]. The central nervous system supervises the maintenance of balance by integrating sensory stimuli from the peripheral nervous system and motor signals from the musculoskeletal system [ 9 , 10 , 11 ]. Postural control is also influenced by genetically determined reactive strategies such as ankle strategies, hip strategies, and steps strategies [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%